Harmonic femtosecond fiber laser based on supercontinuum generation with carbon nanotubes saturable absorber - Siti Norfarha Mat Rifin, 1987-, author; Yusof Munajat, supervisor; Mohd. Zamani Zulkifli, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Ph.D (Fizik)) - Universiti Teknologi Malaysia, 2017